Reducing the Risk of Gout Through Zumba at the Lau Dendang Gymnastics Studio - Suyono, Suyono; Juliani, Afrida; Ritonga, Yunizar; Rahman, Aulia (Jurnal Media Informatika, 2024)
This research aims to find out how to reduce the risk of developing gout through one of the trending sports programs, namely Zumba exercise. So far, research on Zumba has focused on alternatives that can be done by women's exercise groups to reduce pain in areas affected by gout. Rheumatism is a disease that attacks moving parts of the body, namely parts of the body that are connected to one another through joints, causing pain. All types of rheumatism cause annoying pain. Therefore, researchers raised the issue of reducing the risk of developing gout through Zumba. There are many types of sports offered by fitness centers, including gymnastics, Zumba dance, swimming and weight lifting. Because this sport is considered easy to do and fun for the perpetrator. This research uses qualitative research methods using descriptive methods, namely by means of interviews and observation methods. The results of this research are that Zumba is able to reduce uric acid levels, reducing muscle pain. The conclusion of this research is that Zumba exercise can reduce uric acid levels and of course maintain diet.